The Protective Effect of Ethanolic Extract of Mentha spicata Against Irinotecan-Induced Mucositis in mice - Abdul jabbar, Aliaa Abdul sattar; H. Kathem, Sarmed (Iraqi Journal of Pharmaceutical Sciences, 2019)
Irinotecan induced-mucositis is an inflammatory event of intestine caused by an increase in concentration of active metabolite 7ethyl10-hydroxycamptothecin (SN38) in the intestine. Irinotecan must first be converted by a carboxylesterase (CES) to the active metabolite (SN38), which is subsequently glucuronidated by the hepatic enzyme to SN38G. The SN-38G is deconjugated in the intestine to SN-38 via ?-glucuronidase produced by the intestinal bacterial flora, which accounts for SN-38 delayed intestinal mucositis of irinotecan. To study the protective effect of mentha in irinotecan-induced mucositis, intestinal mucositis induced by I.P injection of irinotecan (75mg/Kg/day) for 4 days. Mentha ethanolic extract orally administered to mice for 7 days starting one day before irinotecan dose. Results showed that mentha ethanolic extract significantly decreased both jejunal tissue IL-1? (3.47±1.23 vs 6.5±0.36 ng/ml) and fecal ?-glucuronidase activity (79.78± 10.7 vs 120.6± 8.3 U) compared to model control group. Histopathological sections showed improvements in mucositis features in the mentha extract treated animals compared to the model control mice. As a conclusion, Mentha ethanolic extract has a protective effect on irinotecan-induced mucositis.